Assessment of relationships between novel inflammatory markers and presence and severity of preeclampsia: Epicardial fat thickness, pentraxin-3, and neutrophil-to-lymphocyte ratio - Huseyin Altug Cakmak; Burcu Dincgez Cakmak; Cigdem Abide Yayla; Ebru Inci Coskun; Mehmet Erturk; Ibrahim Keles (Taylor & Francis Group, 2017)
Objective: The aim of this study was to evaluate the relation of three new inflammatory markers with presence and severity of preeclampsia and to compare the predictive values of all markers for presence of this setting. Methods: In this study, a total of 100 consecutive pregnants with a diagnosis of preeclampsia and 40 healthy pregnants between October 2014 and April 2015 were included. Epicardial fat tissue was calculated by two-dimensional transthoracic echocardiography, and pentraxin-3 and neutrophil-to-lymphocyte ratio were measured by using an enzyme-linked immunosorbent assay method and routine blood count analysis, respectively. Results: Epicardial fat thickness (p < 0.001), pentraxin-3 (p < 0.001), and neutrophil-to-lymphocyte ratio (p < 0.001) were found to be significantly increased in the preeclampsia as compared to the healthy pregnants. Furthermore, epicardial fat thickness (p = 0.002), pentraxin-3 (p < 0.001), and neutrophil-to-lymphocyte ratio (p < 0.001) were significantly elevated in the severe preeclampsia compared to mild preeclampsia. In the multivariate analysis, epicardial fat thickness (p = 0.013), pentraxin-3 (p = 0.04), and neutrophil-to-lymphocyte ratio (p < 0.001) were found as significant independent predictors of presence of preeclampsia after adjusting for other risk factors. Conclusion: Epicardial fat thickness, neutrophil-to-lymphocyte ratio, and pentraxin-3 are important markers that provide an additional information beyond that provided by conventional methods in predicting presence and severity of preeclampsia.